Implementasi Role Playing untuk Menanamkan Sikap Toleran terhadap Keberagaman Budaya dan Agama pada Siswa - Meily Aulia Rahmah; Ratna Erviana; Susilo Tri Widodo (ARZUSIN, 2025)
Although a tolerant attitude toward cultural and religious diversity is a key competency in Pendidikan Pancasila instruction at the elementary level, initial conditions among sixth-grade students at SDN Ngaliyan 05 indicated that their awareness of respecting differences and collaborating with peers from diverse backgrounds still needed strengthening. This study aimed to describe the implementation of the role playing model and examine its effectiveness in fostering a tolerant attitude toward cultural and religious diversity among sixth-grade students at SDN Ngaliyan 05. A mixed-methods design combining quantitative and qualitative approaches was employed, involving 29 students as research participants. The learning activities were conducted in two sessions: the first session used a lecture method, and the second session applied the role playing model. Data were collected through tolerance-attitude questionnaires administered in both sessions and observations of learning activities, then analyzed using descriptive quantitative and qualitative techniques. The results showed that in the first session most students were still in the moderate and low categories of tolerant attitude, whereas in the second session, after the role playing model was implemented, there was a significant increase in tolerance, with the majority of students reaching a high category of tolerant attitude. These findings indicate that the role playing model is effective in fostering mutual respect, appreciation of cultural and religious differences, and the strengthening of positive social interactions among students. Accordingly, the application of the role playing model in Pendidikan Pancasila instruction is proven effective in cultivating a tolerant attitude toward cultural and religious diversity among sixth-grade students at SDN Ngaliyan 05 and has implications for its use as an innovative and practical alternative strategy for character education in elementary schools.